Strategi Pemasaran Mebel Kayu Sentra Industri Kecil Pondok Bambu, Jakarta Timur (Wood Furniture Marketing Strategy on Pondok Bambu Small Industry Centre, East Jakarta) - Sudaryanto; Yulius Hero; Dwi Juli Setyowati (Jurnal Manajemen Hutan Tropika, 2008)
Furniture is one of wood products to fulfill the household needs, especially for household furnishing. Wood product which is used for furniture tends to decrease because of the substitution products, i.e.: plastic, rattan, bamboo, glass, and metal. To continue their effort, small industries in Indonesia face hard problems and challanges. To solve the hard problems and challenges, then a new marketing strategy through the study on marketing strategy of small wood-furniture industry is needed. This research objectives are to know several factors which have relation toward marketing of woodfurniture and compile alternative small industrial marketing strategy of wood-furniture. Research conducts in Small Industry Centre, Pondok Bambu, East Jakarta from June to July 2008. Some tools are used in this research, such as: questionaire, calculator, camera, and stationery. The method of data collection is purposive sampling with total amount of responden is 30 people-small industry owners. Data analysis uses regression and SWOT method (Strength, Weaknesses. Opportunities, Threath). Result of the research for the regression equation of wood-furniture marketing Y= 9,001 - 0,6798 X1 - 1,4834 X2 - 1,4834 X3 + 0,4818 X4 with value R2 is equal to 51.3%. Linearity test model indicates that F Calculated is 6.57 in significat level α = 1%. Factors that influence wood-furniture marketing of sale volume are variation of product, wood-furniture price, distribution system and promotion. The relation between sale volume with variable of product variation, wood-furniture price, and distribution system is significant with negative direction. It means that smaller product variation, lower wood-furniture price, and more efficient distribution system; will effect to higher sale volume. Whereas the relation between sale volume with variable of promotion is not significant with positive direction. It means that activity of promotion does not have any effect on sale volume of woodfurniture. This matter is caused by the same source of raw material and product design of woodfurniture which is used by small industry has relatively similar form as source of semi-finished product from Jepara. Market position according to SWOT matrix at 1st Quadrant is called SO ( Strength- Opportunities) position. It means that small industry of wood-furniture has to create strategy by using strength to exploit existing opportunity. Applications of SO strategy are by selling product at cheaper price, improving service to consumer, using strategic location to attract consumer and improving product quality.